BNT162b2 vaccine considerations for immunocompromised individuals: A global perspective. (June 2022) - Jatoi, Hafsa Nazir; Abbas, Samina; Abbasi, Muhammad Saif; Tauni, Misha Asif; Ghazanfar, Shamas; Zafar Malick, Mohammad Daniyal; Umar, Muhammad Faiq; Tahir, Muhammad Junaid; Asghar, Muhammad Sohaib; Ahmed, Ali
Abstract: With the emergence of COVID-19 vaccines, individuals with comorbidities and immunosuppression require particular attention and should be prioritized for vaccination. However, the majority of vaccine clinical trials excluded people with comorbidities, resulting in a lack of data regarding vaccine efficacy in this demographic. Along with more inclusivity in clinical trials, reaching a definitive conclusion regarding vaccine efficacy in these patients is also crucial. In our review, we highlight the BNT162b2 vaccine safety and efficacy based on the limited number of clinical trials which included this demographic. We also provide vaccine considerations for individuals with cancer, autoimmune diseases, HIV, obesity, diabetes, organ transplant recipients and those undergoing maintenance haemodialysis to help them govern their decision regarding vaccine administration. In conclusion, further studies are required to alleviate any insecurities in patients with comorbidities regarding vaccination and it is recommended that patients are monitored post-vaccination to make sure sufficient immunity is achieved. Highlights: With the emergence of COVID-19 vaccines, individuals with comorbidities and immunosuppression should be prioritized for vaccination. In our review, we highlight the BNT162b2 vaccine safety and efficacy in immunocompromised individuals. Further studies are required to alleviate any insecurities in patients with comorbidities regarding vaccination.